Influence of methylcellulose on the impermeability properties of carbon nanotube-based cement pastes at different water-to-cement ratios. (30th May 2020) - Li, Luan; Jing, Hongwen; Gao, Yuan; Hu, Tao; Meng, Yaoyao; Fu, Guangping
Highlights: The reinforcing effects of MWCNTs against w/c ratios were investigated. An appropriate range of MC benefits the impermeability properties of cement. The hybrid MWCNT/MC reinforce the pore structures of cementitious composites. Abstract: The notable mechanical properties of multiwalled carbon nanotubes (MWCNTs) make them a potential reinforcement for cementitious composites. However, the MWCNTs in fresh ordinary Portland cement (OPC) pastes have been reported to agglomerate easily and influences their ability to act as reinforcements, thereby creating a technical barrier for the application of MWCNTs in cement and concretes. In this study, methylcellulose (MC) was selected as an additive to increase the viscosity of the cement-based materials. The effects and mechanisms of the MC on the transport properties and pore structures of the MWCNT-based cementitious composites at different water-to-cement ( w/c ) ratios were studied. Instruments developed in the laboratory were applied to measure two transport properties: water sorptivity and gas permeability. Furthermore, mercury intrusion porosimetry (MIP) and scanning electron microscopy (SEM) was used to further illustrate the pore structure effects from the reinforcements. The results imply that MWCNTs enhanced the impermeability properties of the cementitious composites, and when the w/c ratio increased, the efficiency of the reinforcements was less notable. When extra MC was added into the MWCNT-based cementitious composites, there were two distinct trends: the best water absorption properties of the cement pastes herein appeared at a 0.6 w/c ratio, while the best gas permeability properties herein occurred at a 0.3- w/c -ratio, mainly due to the hygroscopicity of the methylcellulose. The MIP results further suggested that the MC improved the aperture distribution of the MWCNTs in the cementitious composites and greatly optimized the pores from 10 3 nm to 10 2 nm at high w/c ratios. SEM images confirmed that the MC increased the viscosity of the fresh cement pastes and inhibited the reagglomeration of the MWCNTs. The findings of this study can guide MWCNT/MC hybrid composite implementation in the future.